(untitled) (Itinera, 2022)
The anthropological desire to revitalize images runs throughout the history of cinema and is particularly linked to colour and colorization practices. But, as Barthes notes, any attempt to revitalize is nothing more than a cosmetic, the kind used to paint corpses. When we look at a colorized image, we cannot fail to see death beneath the opaque layer of colour. In this article, we highlight and analyse three colorization techniques corresponding to as many attempts to bring images to life (hand painted, rotoscope and AI automatic colour) before proposing colorization as a tactics for the archival image to satisfy algorithmic desire of «survivre».